If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (X + -5) = 16 Reorder the terms: X + (-5 + X) = 16 Remove parenthesis around (-5 + X) X + -5 + X = 16 Reorder the terms: -5 + X + X = 16 Combine like terms: X + X = 2X -5 + 2X = 16 Solving -5 + 2X = 16 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2X = 16 + 5 Combine like terms: -5 + 5 = 0 0 + 2X = 16 + 5 2X = 16 + 5 Combine like terms: 16 + 5 = 21 2X = 21 Divide each side by '2'. X = 10.5 Simplifying X = 10.5
| 5y-4=3y-18 | | 70=x+4 | | 3x^4-16x^2-81=0 | | g(x)=3f(x+1)-1 | | 28=4n+4-8 | | 4(5x-1)-(x+5)=24 | | 7x+145.5=6 | | f(x)=16x^4+8x^2+1 | | tan(19pi/12 | | 0=-2t(8t-75) | | -28=4n+4-8 | | 11x+1=5x+61 | | f(-4)=x^2-3x+9 | | 29=7+x+2 | | 2l+28=58 | | 5(n-4)=25 | | 6y=5(y+9) | | -5=y | | -8x+4(1+5x)=-6x-1 | | 8-6x+3x=-8x-3x | | 8n^2/3 | | 3/20=24/x | | 8a-6=66 | | -4x=20/3 | | 4(x+9)=2x-1 | | -8x+4(1+5x)=-6-1 | | .19x+.33=2.04 | | w*6/e=36 | | -2x+39=x+18 | | 3(x-2)=35.7 | | x^2+y^2-8x-4y+3=0 | | -2x-12=-5x-3 |